The Clinical Features and Long-Term Follow-Up of Vitamin B6-Responsive Infantile Spasms in a Chinese Cohort - Jiao, Xianru; Gong, Pan; Niu, Yue; Xu, Zhao; Wu, Ye; Zhang, Yuehua; Yang, Zhixian (Frontiers in Neurology, 2022)
Objective To analyze the clinical features, treatment, and prognosis of patients with vitamin B6-responsive infantile spasms (IS). Methods The clinical features, genetics, and follow-up data of 30 patients were collected and analyzed. Results The age of epileptic spasms (ES) onset was from 3 months to 12 months. They all received high doses of vitamin B6 at different times after the onset of ES, ranging from 1 day to 5 months. ES were controlled within 11 days in 93% (28/30) patients, and as late as 1 month and 2 months in the other two patients. In the course of treatment, 28 patients were seizure-free all the time, and seizures of other two patients recurred due to withdrawal of vitamin B6. The available follow-up EEG results of 28 patients were normal in 26 cases, and 81% (21/26) had suppressed epileptic discharges within 6 months. Of the 26 cases with normal follow up EEG, 4 had developmental delay and 22 had normal development. The time for EEG to return to normal in 22 patients with normal development ranged from 14 days to 2 years (mean = 111.5 days; median = 52.5 days). The time for EEG to return to normal in the other 4 patients with development delay ranged from 4 months to 2 years (mean = 375 days; median = 330 days). To the last follow-up, seizures were controlled well in 29 surviving patients, and 21 patients were able to deactivate from all medications without seizures recurrence. Sixteen patients showed varying degrees of developmental delay after onset. After seizure control, the psychomotor development was delayed in 7 patients (one died) until the last follow-up. Genetic analysis did not show any meaningful results. Conclusion An observation period of 1–2 weeks is essential to identify patients with vitamin B6-responsive IS. The treatment time could be extended according to the treatment response and EEG changes. It might take a longer time for EEG to return to normal and to stop taking drugs in patients with persistent or unimproved developmental delay. Neurodevelopmental outcomes and prognosis of vitamin B6-responsive IS were relatively favorable.